2021
DOI: 10.1515/eng-2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

Profile of system and product certification as quality infrastructure in Indonesia

Abstract: Quality is a universal standard that is expected by consumers of a product or service used. Consumers in general cannot individually assess this quality, with the help of an independent third party it can be done. The certification body is one element in the quality infrastructure that plays a role in providing quality assurance of products and services according to applicable standards. There are various certification bodies in Indonesia both for system and product certification, the kinds additionally range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
7
0
2
Order By: Relevance
“…It can be concluded that the application of standards provides positive benefits for the industry. This result is in line with the literature study conducted by Isharyadi and Kristiningrum (2021) which shows the benefits of implementing standards in the form of product certification, including cost savings in each of its business chains. In contrast with this, there are still many industries, especially SMEs, which are reluctant to implement standards mainly due to the high cost of SNI certification ( Setyoko et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…It can be concluded that the application of standards provides positive benefits for the industry. This result is in line with the literature study conducted by Isharyadi and Kristiningrum (2021) which shows the benefits of implementing standards in the form of product certification, including cost savings in each of its business chains. In contrast with this, there are still many industries, especially SMEs, which are reluctant to implement standards mainly due to the high cost of SNI certification ( Setyoko et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Some activities, especially conformity assessment, require a competent and independent third party. This is done to ensure the assessment's suitability, such as the principles used in the certification process [20].…”
Section: Mapping Between the Proper Program And Iso 14025 -Type III E...mentioning
confidence: 99%
“…Secara umum dalam mengkonsumsi suatu produk, konsumen tentunya akan menggunakan produk yang berkualitas (Mooij & Hofstede, 2002). Kualitas dalam hal ini dapat diartikan bahwa produk tersebut telah memenuhi pesyaratan teknis yang telah ditetapkan dalam suatu standar, dimana spesifikasi dalam standar tersebut telah memenuhi kebutuhan dari konsumen (Isharyadi & Kristiningrum, 2021). Saat ini, sudah banyak diberikan informasi terkait kualitas dan standar yang melekat pada suatu produk.…”
Section: Kebutuhan Konsumen (Consumer Needs)unclassified